Traffic Engineering Study Through the Implementation of a One-Way System on Suranadi Road on the Performance of the Narmada Intersection Using the PKJI 2023 and PTV VISSIM Methods - Dimas Adin Fajar Nugroho; Anwar Effendy; Ari Ramadhan Hidayat (International Journal of Science and Environment (IJSE), 2026)
The Narmada Intersection at the junction of Jalan Suranadi and Jalan Mataram Sikur experiences traffic congestion due to high vehicle volume, market activity, and side obstacles in the form of on-road parking. This study aims to evaluate the performance of the unsignalized intersection in its existing condition and analyze the effect of implementing a one-way system on the A arm (Jalan Suranadi) on intersection performance. The methods used are the 2023 Indonesian Road Capacity Guidelines (PKJI) and microscopic simulations using PTV VISSIM software. Data were obtained through traffic volume surveys, road geometry measurements, and observations of traffic conditions in the field. The analysis results show that the existing condition has a degree of saturation (DJ) of 0.76 with a delay of 14.99 seconds/vehicle so that the intersection is in a condition close to saturation. The implementation of the one-way outflow scenario (outflow only) resulted in a DJ value of 0.81 with a delay of 15.79 seconds/vehicle, while the one-way inflow scenario (inflow only) resulted in a DJ value of 0.66 with a delay of 13.17 seconds/vehicle. The PTV VISSIM simulation results show that the inflow only scenario provides a better level of service than the outflow only scenario. Overall, the implementation of the one-way inflow system on arm A is considered more effective in improving intersection performance by reducing traffic conflicts and increasing the regularity of vehicle flow.